CAPITAL ASSET PRICING MODEL METHOD: AN ANALYSIS OF PEFINDO 25 COMPANIES RISK AND RETURN LISTED AT INDONESIA STOCK EXCHANGE - Hutabarat, Francis M.; Naomi, Rut (Prosiding Seminar Nasional INDOCOMPAC)
The industry in Indonesia is an interesting business to capitalize. In Indonesia many companies were established since it is profitable. The capital market serves as an economic pillar in most countries. Indonesia is a rich country, rich in many ways especially in natural resources. However, the industry has its ups and downs in the stock market. It is interesting to see the performance of the companies listed in the Indonesia Stock Exchange.  This study aimed to measure and analyze companies listed in Pefindo25 at Indonesian Stock Exchange using Capital Asset Pricing Model. The sample used is 25 companies listed at Pefindo25 index. Based on the results of the study, it can conclude that after analyzing the companies listed in the Indonesian Stock Exchange using Capital Asset Pricing Model that based on Beta analysis, the companies have the type of stocks that are aggressive and defensive. With positive and negative return. The company with aggressive beta shows that the company tend to face higher risk, as JPFA find itself with positif return 15.47% expected return. And companies with defensive type of stocks tend to have positive return such as: FISH, STTP, AISA, APLN, and others since they are not sensitive to market changes. It is recommended for further research to look on this CAPM method in analyzing the stock investment.